Existence of a Short-Run Equilibrium of the Dixit-Stiglitz-Krugman Model. (25th June 2018) - Tabata, Minoru; Eshima, Nobuoki
Abstract : Each short-run equilibrium of the Dixit-Stiglitz-Krugman model is defined as a solution to the wage equation when the distributions of workers and farmers are given functions. We extend the discrete nonlinear operator contained in the wage equation as a set-valued operator. Applying the Kakutani fixed-point theorem to the set-valued operator, under the most general assumptions, we prove that the model has a short-run equilibrium.